2005
DOI: 10.1017/s0024282904014586
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic studies on the Parmotrema reticulatum (syn. Rimelia reticulata) complex, including the confirmation of P. pseudoreticulatum as a distinct species

Abstract: Molecular phylogenetic analyses based on nuclear ITS rDNA and mitochondrial SSU rDNA sequences from 32 specimens representing Parmotrema pseudoreticulatum, P. reticulatum and P. clavuliferum from Africa, Asia, Australia, and Europe are reported. Samples from western Europe and South Africa formed an independent monophyletic group, which belongs to P. pseudoreticulatum, a species not accepted by some recent authors, that has only been reported from Portugal, Spain and Morocco. In contrast, P. reticulatum and P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Other studies confirmed the species status of previously synonymized taxa, e.g. Punctelia jeckeri (P. ulophylla, Crespo et al 2004b;Thell et al 2005) or Parmotrema pseudoreticulatum (Divakar et al 2005a). However, there are exceptions.…”
Section: Lecanoralessupporting
confidence: 63%
“…Other studies confirmed the species status of previously synonymized taxa, e.g. Punctelia jeckeri (P. ulophylla, Crespo et al 2004b;Thell et al 2005) or Parmotrema pseudoreticulatum (Divakar et al 2005a). However, there are exceptions.…”
Section: Lecanoralessupporting
confidence: 63%
“…Cryptic lineages have been reported in various, unrelated groups of fungi, including the Cladia aggregata group (Parnmen 2011), the genus Letharia (Kroken and Taylor 2001), the Parmelina tiliacea aggr. , the Parmotrema reticulatum group (Divakar et al 2005a), and the Rhizoplaca melanophthalma complex (Leavitt et al 2011c). Further, there is evidence for the presence of cryptic lineages in tropical Porina spp.…”
Section: Molecular Studies Addressing Species Delimitations In Lichenmentioning
confidence: 99%
“…For example, several cases have been detected in the Parmeliaceae, where the presence of cryptic species is not restricted to any particular mode of reproduction. Cryptic lineages have been reported in apotheciate taxa such as Parmelina quercina (Argüello & al., 2007), the isidiate Parmelia saxatilis (Crespo & al., 2002;Molina & al., 2004) and the sorediate Parmotrema reticulatum (Divakar & al., 2005b). It should be noted that, although available studies are unequivocal in revealing cryptic lineages within lichen morphospecies, the lack of molecular markers with greater resolution tends to limit studies in some groups of lichens.…”
Section: Cryptic Speciesmentioning
confidence: 99%